Diameter-Height relationship model for Shorea assamica in secondary tropical rainforest, South Borneo - Wirabuana, Pandu; Yusanto Nugroho; Budi Mulyana (Talenta Publisher, 2025)
Diameter-height relationship model is generally developed to facilitate the quantification of tree height at the individual level. However, the model’s reliability principally varies due to the influence of certain factors like site quality and type of species. Thus, a site species-specific model is recommended to support sustainable forest management. This study aims to evaluate the best-fit model for estimating the tree height of Shorea assamica in the secondary tropical rainforest, South Borneo. Data from forest inventory consisting of 1,440 tree diameter at breast height (DBH) and height measurements were used to evaluate five alternative models, i.e., Linear, Power, Exponential, Sigmoid, and Gompertz. These data were randomly split into two datasets, i.e., initial model development (1,009 trees) and model validation (431 trees). The model reliability was assessed and ranked using the coefficient of determination (R2), residual standard error (RSE), akaike information criterion (AIC), mean absolute error (MAE), and root means square error (RMSE). The results of the study obtained an average tree diameter of 42.8 cm with the inverval of 22-99 cm and a mean tree height of 16.6 m with the distribution of 11-31 m. The Power model showed the best fit to explain the relationship model between the diameter and height of the S. assamica with an R2 of 74% and an RMSE of 1.72 m. It indicated Power model could facilitate more efficient tree height estimation of S. assamica in the study site